قراءة تاريخية في الفكر المرجعي لديفاكس - رحماني,صالح; راشدي,محسن; بن زينة,مراد (University of Eloued جامعة الوادي, 2024)
من خلال دراستنا يتضح لنا ان الملك سيفاكسهوأول اقليد لنوميديا الغربية ( الماسيسيل ) حسب ما ورد في المصادر الكلاسيكية، الذي استطاع ان يبسط نفوذه الى نوميديا الشرقية، وتمكن من يحتل مكانة هامة في بلاد المغرب القديم. وفي ضل الصراع القائم في الحوض الغربي للمتوسط بين القوى الكبرى قرطاجة وروما، أراد الملك سيفاكس ان يجنب مملكته والمنطقة مخاطر هذا الصراع، فلجأ الى عقد مؤتمر سيقا الدولي سنة 206ق.م عاصمة مملكة الماسيسيل، والذي يعد اول مؤتمر دولي شهدته المنطقة أواخر القرن الثالث قبل الميلاد جمع بين القائد الروماني سكيبيووالقائد القرطاجي اصدر بعل في طاولة واحدة، من اجل الحفاظ على التوازن الدولي بين القوتين اللتين كانتا تتسابقان لتحالفه، نظرا لأهمية مملكته جغرافيا وعسكريا. وبالرغم من انه كان متحالفا مع الرومان الا انه بعد مؤتمر سيقا تحول الى مناصرة القرطاجيين بعد أن ادرك نوايا الرومان واطماعهم التوسعية في شمال افريقيا.ولكن ذلك لم يمنع الرومان من الدخول الى بلاد المغرب واحتلالها فيما بعد. With reference to the classical sources, our study demonstrated that Syphax is the first king of Western Numidia (Masaesyli) who was able to extend his authority and power to Eastern Numidia. This enabled him to gain an important position in the Ancient Maghreb. In the time of the conflict in the western basin of the Mediterranean between the great powers of Carthage and Rome, the King Syphax wanted to prevent his kingdom and the regionfrom the threats of this conflict. Consequently, he resorted to hold the international conference of Siga in 206 BC, which is the first international conference that the region witnessed, in the late third century BC, which gathered the Roman leader Scipio and the Carthaginian leader Hasdrubal at one table, in order to maintain the international balance between the two powers that were competing for alliancewith Syphaxdue to the importance of the geographical and military position of hiskingdom. Although he was allied with the Romans, after the Sega conference he altered to the Carthaginians when he realised the Romans' intentions and expansionist tendencies in North Africa. However, this did not prevent the Romans from reaching the Maghreb and conquering it later.
من خلال مؤتمر سيقا 602 ق . م
Keywords: سيفاكس; مملكة الماسيسيل; ، سيقا; Syphax; Masaesylikingdom; Siga